Madrasah al-manarah an Islamic approach in providing responsive education for the Muslims in Davao City - Diamla, Abdul Malik M.
Educational facilities play a major role as one of important in a society by transferring their knowledge and values for its continuum on next generations that will follow. In Islamic communities, this important institution is called madrasah. The madrasah is an offshoot of increase of Muslim students studying in masjid, being the locus of a Muslim community. The emergence of this new institution ushered the golden Era of Islamic visualization at the same time when the West is in nadir of their existence. But this doesn't last long and after the two world wars the west turns the table of Muslims societies and the madrasah were left in oblivion and western-oriented schools become the alternative source of seeking knowledge of most Muslim's students. This shift created a two types of Muslims ? one who is studying in a madrasah, knowledgeable about Islamic studies and in the future will be an uztads (Islamic teacher) or alim (Muslim scholar) while the other one is studying to be a doctor in a university. This greatly contradicts the very essence of Islam, which is holistic. Another grave repercussion is that many Muslim nowadays didn't even know the basics of Islamic faith. Together with non-physical problems is the physical one. Most of the madaris are dilapidated and a copied design of secular schools. That many research and studies suggests that it greatly affects the learning of students. In the Philippines, the creation of DepED Order No. 51 recognizes this problem and hopefully this will make opportunities for Muslims to be holistic in their every dealing and have a physical learning environment that shows the local image thru Islamic Architecture that will portray the beautiful message of Islam.